The long-term impact of childhood sexual assault on depression and self-reported mental and physical health - Oluwasegun Akinyemi; Temitope Ogundare; Mojisola Fasokun; Fadeke Ogunyankin; Nkemdirim Ugochukwu; Walia Ajisafe; Seun Ikugbayigbe; Oluebubechukwu Eze; Kakra Hughes; Miriam Michael (Frontiers in Psychiatry)
BackgroundChildhood trauma, including sexual assault (CSA), is a known risk factor for adverse mental health outcomes. This study quantifies the impact of CSA on the likelihood of being diagnosed with depression in adulthood, as well as its influence on poor mental and physical health days.MethodsWe analyzed data from the Behavioral Risk Factor Surveillance System (BRFSS) (2016–2023), comprising 321,106 respondents. The primary exposure was self-reported CSA, while the main outcomes were depression diagnosis, poor mental health days, and poor physical health days. Covariates included race, gender, marital status, employment, age, education, state, year, language spoken at home, metropolitan status, and urban residence. We employed Inverse Probability Weighting (IPW) to estimate the Average Treatment Effect (ATE), controlling for confounders and incorporating state and year fixed effects. Sampling weights ensured national representativeness, and robust standard errors accounted for clustering by state.ResultsIn a matched cohort of 15,150 individuals with CSA and 15,150 controls, the CSA group had an average age of 50.3 ± 16.3 years, with most being White (69.3%) and female (76.7%). CSA was significantly associated with an increased risk of depression diagnosis, with a 22.1 percentage-point increase for those with one CSA experience (ATE = 0.221, 95% CI: 0.192–0.250, p < 0.001) and a 24.4 percentage-point increase for those with multiple CSA experiences (ATE = 0.244, 95% CI: 0.222–0.266, p < 0.001). CSA also impacted mental health. Those with a single CSA exposure reported 2.8 more days of poor mental health per month (ATE = 2.829, 95% CI: 2.096–3.398, p < 0.001), while those with multiple exposures reported 4.2 more days (ATE = 4.175, 95% CI: 3.609–4.740, p < 0.001) compared to controls. Regarding physical health, individuals with one CSA exposure reported 1.5 additional poor physical health days (ATE = 1.538, 95% CI: 0.788–2.289), while those with multiple exposures experienced 2.6 additional days (ATE = 2.587, 95% CI: 1.941–3.232).ConclusionThis study provides robust evidence that CSA significantly increases the likelihood of depression in adulthood and leads to more poor mental and physical health days. The findings underscore the cumulative impact of multiple CSA exposures on health outcomes and emphasize the need for trauma-informed healthcare, early intervention, and public health strategies to mitigate the long-term consequences of CSA.